Insecure Parental Attachment and Anxiety in Vocational College Students: The Mediating Role of Subjective Well-Being and the Moderating Role of Self-Esteem - Hao S; Zhang X; Xu H (Psychology Research and Behavior Management, 2024)
Shuwei Hao,1 Xueting Zhang,2 Honghong Xu1 1Department of Medical Psychology, School of Health Humanities, Peking University, Beijing, 100191, People’s Republic of China; 2Department of Psychology, Ningxia University, Yinchuan, 750000, People’s Republic of ChinaCorrespondence: Honghong Xu, Department of Medical Psychology, School of Health Humanities, Peking University, 38, Xueyuan Road, Haidian District, Beijing, 100191, People’s Republic of China, Email sofiaxuhong@163.comPurpose: Although insecure parental attachment (IPA) has been shown to play an important role in anxiety, little is known about the mediating and moderating mechanisms underlying this relationship.Patients and Methods: In the present study, we examined the mediating role of subjective well-being (SWB) in the association between IPA and anxiety and the moderating role of self-esteem. 947 Chinese vocational college students completed the measures of IPA, anxiety, SWB, and self-esteem.Results: The results indicated that IPA was significantly and positively associated with anxiety, and SWB partially mediated this relationship. Moreover, the results indicated that self-esteem moderated the relationship between IPA and anxiety. The higher the level of self-esteem, the weaker the effect of insecure attachment on the anxiety of vocational college students.Conclusion: This study highlights the significance of identifying the mechanisms of mediating and moderating paths between IPA and anxiety in vocational college students.Keywords: insecure parental attachment, anxiety, subjective well-being, self-esteem, vocational college students